HPS1 Regulates the Maturation of Large Dense Core Vesicles and Lysozyme Secretion in Paneth Cells - Yu, Jiaying; He, Xin; Wei, Aihua; Liu, Teng; Zhang, Qin; Pan, Ying; Hao, Zhenhua; Yang, Lin; Yuan, Yefeng; Zhang, Zhao; Zhang, Chang; Hao, Chanjuan; et al. (Frontiers in Immunology, 2020)
Hermansky-Pudlak syndrome (HPS) is characterized by oculocutaneous albinism, bleeding tendency and other chronic organ lesions due to defects in tissue-specific lysosome-related organelles (LROs). For some HPS subtypes, such as HPS-1, it is common to have symptoms of HPS-associated inflammatory bowel disease (IBD). However, its underlying mechanism is largely unknown. HPS1 is a subunit of the BLOC-3 complex which functions in the biogenesis of LROs. Large dense core vesicles (LDCVs) in Paneth cells of the intestine are a type of LROs. We here first report the abnormal LDCV morphology (increased number and enlarged size) in HPS1-deficient pale ear (ep) mice. Similar to its role in melanosome maturation, HPS1 plays an important function in the removal of VAMP7 from LDCVs to promote the maturation of LDCVs. The immature LDCVs in ep mice are defective in regulated secretion of lysozyme, a key anti-microbial peptide in the intestine. We observed changes in the composition of intestinal microbiota in both HPS-1 patients and ep mice. These findings provide insights into the underlying mechanism of HPS-associated IBD development, which may be implicated in possible therapeutic intervention of this devastating condition.